(t/7)+3=1

Simple and best practice solution for (t/7)+3=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (t/7)+3=1 equation:



(t/7)+3=1
We move all terms to the left:
(t/7)+3-(1)=0
We add all the numbers together, and all the variables
(+t/7)+3-1=0
We add all the numbers together, and all the variables
(+t/7)+2=0
We get rid of parentheses
t/7+2=0
We multiply all the terms by the denominator
t+2*7=0
We add all the numbers together, and all the variables
t+14=0
We move all terms containing t to the left, all other terms to the right
t=-14

See similar equations:

| 14,5=6,5x+2 | | 13+2n,n=2 | | 81=6t-81 | | 5x-7+10x+7=90 | | 308=28(q-982) | | 5m–125=500 | | -3+1-2n+n=3-3n-1 | | 8x-9=19+8x | | 0.66n=-22 | | (8f+1)(7)= | | 5r-9=36 | | ¾x+¼x-6=-5 | | 7-9x2=5x-6 | | 3(9-2b)=30 | | 9-n,n=4 | | 6+2x=100+60 | | 22+10x+8x=58 | | 0.9k=72 | | 8(x-3)=5(x+6) | | 57=-8t-7 | | (10x+5+8x-1)2=7x+8 | | 5a=200 | | 4(1+10x)=4(1+4x) | | 4=8y=10y+14 | | 4x-7)=7x-61 | | (x+35)=109 | | 42-x=37,x | | x-43/4=11/12 | | n-8.25=(-10.5) | | 5m-10=100 | | 8(j-4=2(4j-16) | | 34=-2+9o+16+o |

Equations solver categories